2015
DOI: 10.1002/phar.1553
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Triclosan as an Antimicrobial Hand Soap and Its Potential Impact on Antimicrobial Resistance: A Focused Review

Abstract: Triclosan is a synthetic biocide found in many household products, including antimicrobial hand soap. Levels of triclosan have been found throughout the environment and in human urine, blood, and even breast milk. Increasing levels of exposure to triclosan have led to concerns over the development of resistance to triclosan and cross-resistance to other antimicrobials. We performed a literature search to assess whether the widespread use of triclosan displays a favorable benefit: risk ratio, defined by evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(53 citation statements)
references
References 54 publications
(108 reference statements)
0
52
0
1
Order By: Relevance
“…They concluded that there was no beneficial effect of triclosan over nonantimicrobial soap, and triclosan resistance has been demonstrated. They concluded that the risks outweighs the benefits of triclosan use (124).…”
Section: Triclosanmentioning
confidence: 99%
“…They concluded that there was no beneficial effect of triclosan over nonantimicrobial soap, and triclosan resistance has been demonstrated. They concluded that the risks outweighs the benefits of triclosan use (124).…”
Section: Triclosanmentioning
confidence: 99%
“…The combined surveillance would also facilitate monitoring of the impact of interventions aimed to improve antibiotic stewardship and reduce consumption [9]. The widespread use of biocidal soaps and gels versus simple soap hand washing and the benefits of potentially reducing the spread institutional infections versus contributing to AMR is another area for consideration [25]. Rushton (2015) [14] stated that antimicrobials should be seen as a common good.…”
Section: Why a One Health Approach And Fully Integrated Surveillance mentioning
confidence: 99%
“…For instance, it has been regularly demonstrated in the laboratory that resistance to triclosan, an antimicrobial agent used in many household products including hand sanitizer, and crossresistance to antimicrobials increases with use of triclosan containing products; however these results have not yet been observed in the community. Based on the available evidence, the risk of potential antimicrobial resistance outweighs the benefit of widespread triclosan use in antimicrobial soaps [57].…”
Section: Antibiotic Resistancementioning
confidence: 99%